Lymph node evaluation and survival after resection of colorectal cancer - Lutfi Soylu; Oguz Ugur Aydin; Nedim Cekmen; Fuat Atalay (Medicine Science, 2017)
Recent studies have demonstrated that lymph nodes ratio (LNR) might provide a significant prognostic role for colorectal cancer. We retrospectively analyzed the data of the patients with colorectal cancer and assessed a possible correlation between lymph node parameters and survival. We conducted a retrospective chart review of patients who underwent a radical colon surgery involving removal of mesocolic lymph nodes due to colorectal cancer. Prognostic significance of the removed lymph node number (LNs), metastatic LNs, lymph node ratio (LNR) and other factors were compared. This retrospective study included 190 patients (117 males and 73 females). The estimated survival period was found to be 87.70 months [confidence interval (CI) of 95% (80.64-94.76)]. LNR, LNs and N stage were found to have significant correlation with survival. Among these factors, LNR had the biggest correlation (r = 0 .138, P =0.028). Multivariate regression analysis of survival with lymph node parameters showed that LNR and N stage were significantly correlated with survival. However, LNR was found to be the most significant prognostic factor [P >0.0001, 95% CI; 3.12 (1.55-5.75)]. LNR is a better prognostic factor in patients with colorectal cancer compared to lymph node stage and number. [Med-Science 2017; 6(2.000): 182-8]